Government Policy in Strengthening Education Quality Assurance in Islamic Education Institutions - Indana, Nurul; Mustofa, Ali; Qomar, Mujamil; Aziz, Abd; Junaris, Imam (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This article discusses government policies to strengthen education quality assurance in Islamic educational institutions. This is library research, with documentary data collection methods analysis using content or content analysis. The results showed that the education quality policy refers to eight SNP: Content Standards, Process Standards, Graduate Competency Standards, Educator and Education Personnel Standards, Management Standards, Facilities and Infrastructure Standards, Financing Standards, and Assessment Standards. Of the eight National Education Standards, each has its policy. To measure the implementation of quality standardization nationally, which includes 8 (eight) national standards of education, measuring the achievement of reference standards and evaluating the quality of education is carried out on educational units/programs through 1). Education Unit/Program Self Evaluation (EDS); 2). Monitoring of Education Units/Programs by Local Government (MSPD); 3). Accreditation; 4). Certification; 5). National Examination; and 6). Database and Information Data Collection. The conclusion of the quality assurance system policy is divided into SPMI and SPME. The internal campus carries out SPMI, while SPME is external if the school is BAN SM and the college is BAN-PT and LAM.